Graines d'histoire - Claire Newton; Jean-Frédéric Terral; Sarah Ivorra; Muriel Gros-Balthazard; Claire Tito de Morais; Sandrine Picq; Margareta Tengberg; Jean-Christophe Pintaud (Revue d'ethnoécologie, 2013)
The main aim of this work is to understand the origin, history, historical biogeography, and mechanisms of date palm domestication (Phoenix dactylifera L.). For that purpose, the morphological diversity of the date palm was studied through seed shape analysis, using the Elliptic Fourier Transforms (EFT) method.The biological material used comprises seeds of uncultivated Phoenix individuals from isolated Oman populations, cultivated date palm varieties, and other related Phoenix species. The results show that Phoenix dactylifera can be differentiated from other species. We could also characterize ancestral seed shape features present in uncultivated populations. Within Phoenix dactylifera, the agrobiodiversity appears complex in terms of geographical structure; the distribution pattern of seed shapes points to human dispersal routes that spread cultivation from one or more initial ‘domestication centres’.In addition, this work provides a powerful tool to identify ancient forms as demonstrated by the analysis of well-preserved desiccated seeds from Egyptian archaeological sites (14th c. BCE - 8th c. CE) compared to the morphometrical reference model based on the analysis of modern material. Allocation of archaeological seeds to different modern Phoenix forms and date palm morphotypes reveals ancient forms consumed and/or exploited in Egypt, and finally evidence spatialized developments of the agrobiodiversity.